2019
DOI: 10.1371/journal.pone.0221549
|View full text |Cite
|
Sign up to set email alerts
|

Independent and concomitant associations of gestational diabetes and maternal obesity to perinatal outcome: A register-based study

Abstract: Aims Gestational diabetes (GDM) is often accompanied by maternal overweight. Our aim was to evaluate the separate and concomitant effects of GDM and maternal overweight/obesity on perinatal outcomes. Methods We used the Finnish Medical Birth Register to identify all 24,577 women with a singleton pregnancy who delivered in 2009 in Finland and underwent an oral glucose tolerance test (OGTT). Women were divided into groups according to the result of OGTT (GDM/no GDM) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
62
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 25 publications
11
62
5
1
Order By: Relevance
“…Several studies have reported maternal obesity as an independent risk factor for newborn macrosomia (17,(23)(24)(25). Pre-gestational BMI is a documented factor that affects fetal growth (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported maternal obesity as an independent risk factor for newborn macrosomia (17,(23)(24)(25). Pre-gestational BMI is a documented factor that affects fetal growth (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, studies in Pima Indians, a population with a high prevalence of T2DM, have revealed sibling discrepancies, with a higher incidence of diabetes among siblings born after maternal diagnosis of diabetes when compared to siblings born before the maternal diagnosis of diabetes [48]. Nevertheless, caution should be taken, as women with diabetes during pregnancy are more likely to be overweight or obese, and obesity per se has adverse effects on the offspring [49]. In order to determine the specific role of the hyperglycemia per se in the adverse outcomes of the progeny, the HAPO (Hyperglycemia and Adverse Pregnancy Outcome) study, analyzing a multiethnic cohort of 25,505 pregnant women with glucose levels below GDM threshold at 15 centers in 9 countries, demonstrated that maternal glucose levels during pregnancy were associated with birth weight and newborn adiposity [50].…”
Section: Adverse Outcomes Of Gdmmentioning
confidence: 99%
“…O sobrepeso e a obesidade são fatores de risco para doenças crônicas e degenerativas, e quando associada à gestação, elevam o risco para complicações maternas, fetais e neonatais (Ijas et al, 2019). Complicações maternas, ocorridas durante o trabalho de parto/parto/puerpério, como pré-eclâmpsia, diabetes mellitus gestacional, teste de tolerância à glicose diminuída, ruptura prematura de membranas, placenta prévia, anemia, oligodrâminio, taxas de cesarianas, laceração vaginal e perineal e hemorragias pós-parto foram associadas à obesidade.…”
Section: Introductionunclassified